Adaptation process of the Inventory of the help relationship of G.T. Barrett-Lennard. - Celis H., Alejandro (Revista de Psicología, 1999)
This paper presents the initial steps of an adaptation to Spanish of the OS-M-64 version of G.T. Barrett-Lennard`s Relationship Inventory. Also discussed in the article are the importance of the relationship’s "receptor" point of view, the usefulness of the questionnaire and different aspects and difficulties related to the methodology used in its adaptation. Also included are a complete version of the Inventory and instructions for its use.